2005
DOI: 10.1029/2004gl020664
|View full text |Cite
|
Sign up to set email alerts
|

Polar vortex controls coupling of North Atlantic Ocean and atmosphere

Abstract: [1] The structure of the North Atlantic leading atmospheric winter variability mode strongly depends on the state of the polar stratospheric vortex. If the polar vortex is strong, one teleconnection pattern emerges in the upper troposphere, while two mostly independent ones appear when the vortex is weak. The anomaly patterns associated with the different polarities of these modes show strong differences in the wind fields and in the correlation of atmospheric variability with the sea surface temperature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Note also that the sunspot number in the winter 2015/2016 was low, which is also favorable for a strong stratospheric polar vortex [ Labitzke and van Loon , ; Shindell et al ., ]. Because of weaker tropospheric forcing, the strong polar vortex signals propagated downward into the troposphere and affected the hemispheric‐scale zonal flow, which is analogous to the results of Perlwitz and Graf [] and Graf and Walter []. This resulted in the strongly positive AO.…”
Section: Discussionsupporting
confidence: 72%
“…Note also that the sunspot number in the winter 2015/2016 was low, which is also favorable for a strong stratospheric polar vortex [ Labitzke and van Loon , ; Shindell et al ., ]. Because of weaker tropospheric forcing, the strong polar vortex signals propagated downward into the troposphere and affected the hemispheric‐scale zonal flow, which is analogous to the results of Perlwitz and Graf [] and Graf and Walter []. This resulted in the strongly positive AO.…”
Section: Discussionsupporting
confidence: 72%
“…Austin (1980) has shown that the stationary planetary waves in the atmosphere, which can propagate vertically into the stratosphere, can influence the variation of blockings. The polarity of NAM and associated stratospheric polar vortex strength can in turn change the stratosphere-troposphere coupling process (Perlwitz and Graf, 2001) and associated tropospheric circulation (Thompson and Wallace, 2001;Wallace and Thompson, 2002;Graf and Walter, 2005) by modulating the vertical propagation of atmospheric waves and related wave-flow interactions. As the Ural blocking is related to the stratospheric polar vortex (Figure 1(c)), in this section, we will explore why the signal of Ural blocking propagates more eastward to East Asia after mid-1970s from the perspective of NAM-related stratospheric polar vortex and associated atmospheric stationary waves.…”
Section: Observationsmentioning
confidence: 99%
“…Stratospheric forcing, resulting from internal 2 Advances in Meteorology the weak polar vortex anomalies could propagate within the stratosphere down to the tropopause. These anomalies can persist for up to 60 days, favor tropospheric anomalies with the same signs as those in the stratosphere, and influence surface storm tracks, surface pressure [19], and North Atlantic sea surface temperatures [20]. Furthermore, Manzini et al [21] showed that the sea level pressure, surface temperature, and sea ice coverage anomalies in the Northern Hemispheric mid-and high latitudes can be traced back to the long-lasting stratospheric vortex anomalies on interdecadal time scales.…”
Section: Introductionmentioning
confidence: 98%